Mutational landscape of retinoblastoma 1(RB1) gene in bladder cancer: insights from a Bangladeshi patients cohort (Dhaka University Journal of Biological Sciences, 2025)
Bladder cancer is a significant health concern in Bangladesh, yet molecular studies on its genetic drivers remain limited. The Retinoblastoma 1(RB1) gene, a pivotal tumor suppressor regulating cell cycle progression, is frequently altered in various malignancies, including bladder cancer. Mutations in exons 18, 22, and 23 of RB1 are particularly critical, as they affect key functional domains of the pRB protein. This study aimed to evaluate the mutational status of these exons in a cohort of Bangladeshi bladder cancer patients. A total of 40 histopathologically confirmed bladder cancer tissue samples were collected from patients treated at the National Institute of Cancer Research and Hospital (NICRH), Dhaka. Genomic DNA was extracted and exons 18, 22, and 23 of RB1 were amplified via PCR using specific primers. Amplicons were verified by agarose gel electrophoresis and subsequently analyzed through Sanger sequencing. High-quality sequence reads were aligned against the reference RB1 gene to identify mutations. Despite previous reports of frequent RB1 mutations in these exons in other populations, no mutations were detected in any of the 40 samples analyzed. The findings suggest possible population-specific genetic variation and indicate that other exons or regulatory mechanisms may play a more prominent role in RB1 inactivation in Bangladeshi patients. This study contributes novel data to the molecular understanding of bladder cancer in Bangladesh and highlights the need for broader genomic and epigenetic investigations to uncover relevant biomarkers in this population.Dhaka Univ. J. Biol. Sci. 34(2): 1-11, 2025 (July)